Compensation method of geodynamic trend in the systems of geoelectric control - Vasilyev, Gleb S.; Kuzichkin, Oleg R.; Grecheneva, Anastasia V.; Dorofeev, Nikolay V. (International Journal of Engineering and Technology, 2018)
To ensure the safety of important national economic objects in the conditions of technogenic, biogenic and anthropogenic interference, it is advisable to carry out automated electromagnetic control of geodynamic processes on the basis of multipolar sensing systems. The paper substantiates the use of methods of compensation of geodynamic variations to increase the sensitivity of multipolar geoelectric control sys-tems. The developed method involves the implementation of compensation of changes in the components of electric field in the control points caused by the natural geodynamic mismatch of the probing system from the object under study, using additional sources. Selection of sources parameters is based on the solution of an approximation problem of the variations of the transverse and longitudinal field compo-nent caused by the geodynamics of the controlled medium. Mathematical modeling has confirmed high accuracy of compensation of real geoelectric fields by the field of additional sources in the conditions of both narrow and wide area of location of the receiving electrodes of the probing installation, which determines an efficiency of the method in the conditions of complex construction, typical for most geotech-nical objects.